A spatiotemporal restoration of partial color artifacts in archival films. Issue 7 (October 2016) - Yadav, Ravindra; Bhattacharya, Saumik; Venkatsh, K.; Gupta, Sumana
Abstract With the rapid growth in video technology and marketability of all forms of visual media, we encounter the need to exploit archive material more effectively and guarantee picture quality. Old films and video often get corrupted by many artifacts due to extensive usage or improper storage. These defects not only lead to reduction in perceptual quality, but also require large transmission bandwidth. In this paper, we present a novel method to restore color image sequences corrupted by partial color artifact. This degradation visible in old color film/video appear as random color patches in the frames. It reduces the perceptual quality of the video. The proposed approach minimizes a convex function, formulated as rank minimization problem, seeking the temporal correlation among the frames in a video sequence. The main feature of the proposed algorithm is its accurate detection and fast restoration of the artifacts present in a video shot.